2013
DOI: 10.4314/tjpr.v12i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Glutaraldehyde-Crosslinked Chitosan Microparticles for the Delivery of Ibuprofen

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
(26 reference statements)
0
12
0
9
Order By: Relevance
“…Many researches were devoted to the development and characterization of microparticles for the delivery of ibuprofen [17,[35][36][37][38][39][40]. For instance, Zhang et al [36] concluded that trehalose and glucose are effective cryoprotectants and mannitol and sucrose are not very good cryoprotectants for the ibuprofen-loaded solid lipid microparticles as they crystallize during the freeze-drying process.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches were devoted to the development and characterization of microparticles for the delivery of ibuprofen [17,[35][36][37][38][39][40]. For instance, Zhang et al [36] concluded that trehalose and glucose are effective cryoprotectants and mannitol and sucrose are not very good cryoprotectants for the ibuprofen-loaded solid lipid microparticles as they crystallize during the freeze-drying process.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mixture was poured into a separatory funnel and allowed to stabilize. After 15 hours, the upper toluene layer saturated with glutaraldehyde was decanted and used as the glutaraldehyde saturated toluene solution [24].…”
Section: Preparation Of Microparticlesmentioning
confidence: 99%
“…The complex coacervation technique requires anionic materials that are used for the ionic interaction with protonated chitosan such as vanillin [83], carrageenan [82], alginate [86], gelatine [87,88], gum Arabic [89], etc. Besides, the addition of crosslinking agent improves the mechanical property of chitosan microcapsules such as sodium tripolyphosphate [90][91][92], sodium hydroxide [93,94], genipin [87,88,95] glutaraldehyde [96], tannic acid [97], etc. In the processing of microcapsule with chitosan, a soluble chitosan is prepared in solvent such as acetic acid [89], citric acid [83], etc.…”
Section: Microencapsulation Processesmentioning
confidence: 99%